THE INFLUENCE OF PROBLEM BASED LEARNING MODELS HELPED BY INSHOT VIDEO LEARNING MEDIA ON ENERGY LITERACY ABILITY LEARNERS - Ramadania; Rahmawati; Fiskawarni, Tri Hastiti (Jurnal Keguruan dan Ilmu Pendidikan (JKIP), 2023)
This study aims to 1) Describe the Energy Literacy Skills of students using the Problem Based Learning learning model. 2) Describe the Energy Literacy Skills of students using the Problem Based Learning learning model without the help of inshot videos. 3) Describe the influence of the Problem Based Learning model assisted by inshot videos on the energy literacy skills of class X students. This type of research is a quasi-experiment (pseudo-experiment). The design of this study is Non-equivalent Control Group Design. The population of this study was all class X students of SMA Negeri 29 Bone in the even semester of the 2024/2025 academic year. The sample of this study was class X E1 consisting of 20 people as the experimental class and class X E2 consisting of 20 people as the control class. The data collection method was carried out using the test method, namely the test instrument (description). The data obtained were analyzed using descriptive analysis techniques and inferential analysis, namely hypothesis testing. The results of this study indicate that: 1) The Energy Literacy Ability Level of Class 2) The Energy Literacy Ability Level of Class 3) There is a significant influence of the Problem Based Learning learning model assisted by video inshot learning media on the Energy Literacy Ability of students in the experimental class with a hypothesis test coefficient value of 0.001 <0.05.